The RHOMOLO economic impact assessment of the R&I and Low-Carbon ERDF Investment programme in Apulia, Italy - Francesco Di Comite; Olga Diukanova; Giovanni Mandras; Javier Gómez Prieto (European Commission, Joint Research Centre (JRC), 2018)
In this note we present the economic impact assessment of the European Regional Development Fund (ERDF) for thematic objectives TO1 "Research and innovation" and TO4 "Low-carbon economy" in the region of Apulia, Italy. The results are based on the RHOMOLO-IO demand multiplier analysis and on computer simulations with the multi-regional dynamic computable general equilibrium (CGE) model RHOMOLO. The former approach is used to calculate the sector-specific output multipliers following a demand-side shock, while the CGE simulations provide evidence of significant spillover effects spreading beyond the Apulian borders and stimulating economic growth in other regions with significant trade links with Apulia. Our results suggest that a exteuro536 million increase in demand for the Manufacturing & Construction sector would entail an increase in total value added of exteuro329 million, which is roughly 0.46% of the regional GDP. The RHOMOLO simulations show that the effects of policy interventions reach their peak in the last years of ERDF programming period (2020-2022), when the absorption of investment funding is at its full potential. In 2022, T01 and T04 investments of the ERDF increase Apulian by 0.2% above the baseline GDP projections. Given the high import intensity of the region, only one fourth of the overall effect is driven by the direct investments and three fourths depend on the productivity improvements achieved as a result of the specific policy design. This demonstrates that the implementation of policies that are effective in raising productivity ensures long term economic benefits even in the absence of continuous funding.
Keywords: C54; C68; E62; 330; rhomolo; region; growth; smart specialisation; investment; impact assessment; modelling